Reporting quality of systematic reviews with moxibustion - Ran Tian; Xuan Zhang; Si-Yao Li; Qi-Ying Aixinjueluo; Wai Ching Lam; Zhao-Xiang Bian (BMC, 2020)
Abstract Background Moxibustion is one of the major interventions of Chinese medicine (CM). The systematic reviews (SRs) are essential references for evaluating the efficacy and safety of moxibustion interventions. This study aimed to assess the reporting quality of these SRs, particularly whether necessary information related to moxibustion was adequately reported. Methods Seven databases (including four English and three Chinese databases) were systematically searched for SRs of moxibustion that were published up to 31 December 2019. The primary analysis was to assess their reporting quality based on 27-item of the Preferred Reporting Items for SRs and Meta-Analyses (PRISMA) and 14-item of moxibustion-related information designed according to CM theory and the STandards for Reporting Interventions in Clinical Trials Of Moxibustion (STRICTOM). Descriptive statistics were also used to analyze their baseline characteristics. Results A total of 97 SRs of moxibustion were identified from 2011 to 2019. For 27-item of PRISMA, except item 5, 8, 16 and 23, the remaining 23 items had the reporting compliances higher than 55%, of which 2 items (item 20 and 26) were fully reporting (100%). However, for moxibustion-related information, 69.1% (67/97) SRs did not provide the specific type of moxibustion, 39.2% (38/97) lacked details regarding the materials, procedure and technique used for moxibustion, 67.0% (65/97) did not report the selection criteria of acupoints for moxibustion, 28.9% (28/97) did not provide the number or duration of treatment sessions, 69.1% (67/97) did not provide any information about safety evaluation, and 94.8% (92/97) SRs did not report the treatment environment. For 51 (55.4%) of 92 SRs that included meta-analysis, it was impossible to assess whether meta-analysis had been properly conducted due to inadequate reporting of moxibustion interventions. Conclusion The reporting quality of SRs of moxibustion need further improvements in terms of adequate reporting of moxibustion interventions and of moxibustion-related rationales. Reporting guideline of "PRISMA extension for moxibustion interventions" should be developed thus to improve their quality.